Meruntuhkan Hambatan: Meninjau Ulang Peran Pemerintah dalam Pengembangan Destinasi Wisata di Indonesia - Ahmad Hudaiby Galih Kusumah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Stakeholder involvement is essential to destination development. They may serve as catalysts or impediments to the growth of tourist sites. This study explores the barriers to tourism destination development associated with the role of local tourism authorities. A qualitative approach, employing semi-structured interviews, was utilized to examine the root causes of these challenges. Sixteen stakeholders, including ten government officials responsible for regional tourism development and six community leaders, were selected as informants in this study. Thematic analysis was used to analyze the interview data. The investigation revealed four main barriers to destination development from government agencies. There are bureaucratic hurdles, contrived program activities, overlapping roles of local governments, and the community’s misconceptions about the government’s role in destination development. These factors collectively hinder the successful implementation of government-led tourism programs. The study suggests that understanding and addressing these barriers are vital to fostering a progressive, sustainable, competitive tourist destination. On a practical level, the findings can help policymakers redesign their strategies to create more community-centric programs, clearly define roles, and manage community expectations. Conceptually, this study expands the existing literature on the role of government and bureaucracy in developing tourist destinations. The study highlights the importance of a participatory approach that engages all stakeholders in the planning and implementation tourism policies and programs.